YIELD OF Coffea arabica GRAFTED ONTO Coffea canephora IN SOILS INFESTED WITH NEMATODES IN MEXICO - García, Francisco Javier López; Castillo, Juan Guillermo Cruz (Coffee Science - ISSN 1984-3909, 2019)
The total of three consecutive years of fruit production was evaluated in six coffee cultivars (Coffea arabica L.) propagated by seed and grafted onto Robusta (Coffea canephora var. Robusta). The plantations were established at 640 m, 920 m, and 1340 m altitude in the central region of the Veracruz State, Mexico. The coffea plants were established in soils naturally infested with nematodes. Grafted plants had higher production than those propagated by seed. Fruit production was higher at 640 m and 920 m than at 1340 m for the two types of propagation. The cultivars Colombia Brote Café and Colombia Brote Verde had the highest fruit yield regardless of the propagation methods; in contrast, Pacamara, had the lowest. The grafted coffee plants that were planted at 1340 m had a yield reduction of 27% in comparison with those at 640 and 920 m. When the Costa Rica 95 variety was grafted, it achieved fruit yield similar to Colombia Brote Verde and Colombia Brote Café. Pacamara produced almost 28% more fruit when it was grafted onto Robusta.